Risk factors for gastroschisis: A case–control study in a Brazilian population. Issue 3 (31st March 2020) - Freitas, Amanda B.; Centofanti, Sandra F.; Osmundo‐Junior, Gilmar S.; Rodrigues, Agatha S.; Francisco, Rossana P. V.; Brizot, Maria L.
Abstract: Objective: To evaluate risk factors associated with fetal gastroschisis. Methods: As a secondary aim of a larger case–control study, pregnant women attending the Fetal Medicine Unit at the Department of Obstetrics and Gynecology at Hospital das Clinicas, Sao Paulo University Medical School between July 1, 2013, and July 31, 2015, were allocated into either the gastroschisis group, where the woman was carrying a fetus with gastroschisis, or the control group, where the fetus was normal. Patients in the control group were matched at study entry for maternal age, preconception body mass index and weeks of gestation. In‐person interviews were conducted during pregnancy to obtain data on demographic, medical, and social characteristics; exposure to substances; pregnancy history; the presence of chronic disease, urinary tract infections (UTIs), influenza, and fever; and the occurrence of stress events between the month before the last menstrual period and the first trimester of pregnancy. Results: Of 171 women included in the study, 57 were allocated to the gastroschisis group and 114 to the control group. There were significant associations between gastroschisis and maternal UTI ( P =0.011), tobacco use ( P =0.001), alcohol consumption ( P ≤0.001), and illicit drug use ( P =0.012). After analysis by standard logistic regression, the remaining significant factors were UTI, tobacco use, and alcohol consumption. Conclusion: UTI and exposure to tobacco or alcohol just before conception and during early pregnancy were associated with an increase in the likelihood of fetal gastroschisis. Abstract : Urinary tract infection, smoking, and alcohol use during the periconception period increased the chance of gastroschisis, with urinary tract infection having the strongest association.